Women Independence Reflected in Anime Spy x Family (2019): A Feminist Perspective - Mawsali, Aluf; Amalia, Syahara Dina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to find out the forms of independence possessed by female characters in the anime Spy x Family and the impact of independence in their lives. This research is a descriptive qualitative research and uses feminist perspective as its approach. Data were collected by note taking and then analyzed using triangulation. The results show that there are four forms of independence possessed by the main female characters in the series, namely: 1) emotional independence, 2) economic independence, 3) intellectual independence, and 4) social independence. This independence has several impacts on their lives, such as: avoiding unwanted things, fulfilling life needs, helping to get out of unfavourable situations, and providing a sense of satisfaction with oneself.